MEASURING STUDENT INTEREST IN CONTINUING DISTANCE LEARNING (PJJ) VIA OPEN LEARNING: MODEL EXPECTATION CONFIRMATION - Marsha Anindita; Dewi Sartika; Joko Sabtohadi (Jurnal Scientia, 2022)
At the beginning of 2020, all countries in the world were hit by the Covid-19 Virus pandemic. This pandemic has prompted the government and numerous business sectors to adjust in carrying out their business activities. One sector that has experienced massive changes in this adjustment is the education sector in Indonesia. This research was conducted to find out how the impact of distance learning policies carried out by the government on student interest in continuing their education. The model used in this study is a confirmation expectation model. There are 240 respondents obtained in this study who are students of the Muhammadiyah University of East Kalimantan who actively use the Open Learning platform. The results of this study indicate that there are some variables that significantly affect student interest in continuing distance learning (PJJ) through the Open Learning platform.